The Analysis of Students Misconceptions by Using Four-Tier Diagnostic Test on Periodic Table of the Elements Lesson - Yanti, Riska; Yasthophi, Arif (Universitas Lampung, 2024)
Periodic Table of the Elements is an abstract topic with many new terms and vocabularies, encompassing subjects such as groups, periods, and periodic properties of elements—such as atomic or ionic radius, ionization energy, electronegativity, electron affinity—as well as the physical and chemical properties of elements. These characteristics make it a challenging topic often leading to misconceptions. This research aimed at finding out student misconceptions regarding Periodic Table of the Elements lesson and finding out the extent of these misconceptions. Mixed method was used in this research with explanatory sequential design. The samples consisted of 35 the eleventh-grade students of class A1 at State Senior High School 1 Rambah, and they were selected by using purposive sampling technique. The instruments of collecting data were four-tier diagnostic test, interview, and documentation. The research findings showed that misconceptions were present across all concepts tested within Periodic Table of the Elements lesson. The highest rate of misconception, 53%, was found in indicator (6), determining the relationship between an element electron configuration and its group placement in the periodic table. The lowest rate of misconception, 11%, was observed in indicator (4), determining isotopes, isobars, and isotones. The mean percentages of student concept comprehension level on Periodic Table of the Elements lesson at the eleventh-grade of class A1 at State Senior High School 1 Rambah were 32% of students understanding the concepts with moderate criterion, 19% of students partially understanding the concepts with moderate criterion, 38% of students experiencing misconceptions with moderate criterion, and 11% of students who did not understand the concepts with low criterion.Keywords: Misconceptions, Four-Tier Diagnostic Test, Periodic Table of the Elements DOI: 10.23960/jppk.v13.i3.32640